RANCANG BANGUN ALAT PRESS SISTEM HIDROLIK DUA ARAH - Iqbal Kurniawan; Ajid Fathurahman; Indra Suyipto; Rodika, M.T.; Subkhan, M.T. (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
Hydraulic press tools are usually used in work in the pressing field. The compaction process is a process of forming a powder into a component by using a certain mold. During the compaction process, the metal powder is placed in the mold, then pressure is placed on the mold so that the powder in the mold will be formed following the shape of the mold cavity. The compaction process is carried out by the method of one action compaction pressure and two action compaction pressure method. In the one-action pressing process, the upper cylindrical shaft moves downward pressing the workpiece and for the two-action pressing process, the upper and lower cylindrical shafts move in opposite directions simultaneously pressing the workpiece from the two upper and lower sides. Therefore, in this final project a two-way hydraulic system press is designed which is expected to help the needs of the metal powder compaction process. This two-way hydraulic system press is designed using a bottle jack with a capacity of 10 tons with a large enough capacity. In the research method, the authors collect data, conceptualize, design, make components, assembly, testing and report generation. The results of trials that have been carried out with a two-way hydraulic system press are able to produce the highest pressure of 4000 PSI. These results have not reached the minimum pressure for compacting aluminum powder, which is 5000 PSI.